2021
DOI: 10.1177/0192513x211068921
|View full text |Cite
|
Sign up to set email alerts
|

Family Strength During the COVID-19 Pandemic in Indonesia

Abstract: Research on family strength is growing. Limited work has been studied about family strength during the COVID-19 pandemic in Indonesia. This qualitative online survey studied on 65 participants, aged 27–57 years (M = 40.85, SD = 6.8), to explore the characters of Indonesian family strength during the COVID-19 pandemic. Qualitative data were analyzed thematically. This research discovered eight characters of Indonesian family strength, namely:(1) intense and open communication, (2) intimacy and time together, (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…The components of psychological capital that contribute significantly to family resilience are self-efficacy and optimism. These findings support previous research that found that self-efficacy and optimism are protective factors against the psychological effects of the pandemic and can reduce symptoms of posttraumatic stress caused by the pandemic [41]; [42]; [32]; [40]. Other research also suggests that optimism is a trait that can promote the development of family resilience [43]; [44]; [45].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The components of psychological capital that contribute significantly to family resilience are self-efficacy and optimism. These findings support previous research that found that self-efficacy and optimism are protective factors against the psychological effects of the pandemic and can reduce symptoms of posttraumatic stress caused by the pandemic [41]; [42]; [32]; [40]. Other research also suggests that optimism is a trait that can promote the development of family resilience [43]; [44]; [45].…”
Section: Discussionsupporting
confidence: 89%
“…The finding of high family resilience in this study is because some families have one of several family strength characteristics that grew during the pandemic in Indonesia. [32], in their research, explained that despite facing challenges and various pressures, resilient families show growth with some of the strong characters they have. These strengths are open communication, intimacy, cooperation, problem-solving, financial stability, spirituality, gratitude, and optimism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 17 students (4.66%) confirmed that they had been infected with COVID-19 and 24 students (6.58%) confirmed that their family members were also infected with COVID-19. Even though these students are in a high-risk zone, they apply strict health protocols, increase their immune system by consuming healthy foods and vitamins, and doing exercises (Valentina & Nurcahyo, 2021). This is in line with the Indonesian Governmentʼs policies, which conveyed through various media including social media and television so that people strictly implement health protocols.…”
Section: Introductionmentioning
confidence: 66%
“…This is also supported by research released by Pew Research Center that Indonesia is one of the religious country who believe that religion has a big impact in their live (Poushter & Fetterrolf, 2019). Valentina and Nurcahyo (2021) found that during the COVID-19 pandemic, individuals as well as families in Indonesia had more opportunities to worship God, such as praying with all family members at home. Prayer indicates believing that God will protect and provide a way out of facing problems caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%